Silicon And Its Relationship With Germination And Related Indices In Varieties Of Solanum lycopersicum L. Under Salinity Conditions - Enríquez-Acosta , Emmanuel Alexander; Ledea-Rodríguez, José Leonardo; Carballo-Méndez, Fernando de Jesús; Ruiz-Espinoza, Francisco Higinio; Beltrán-Morales, Félix Alfredo (REVISTA TERRA LATINOAMERICANA, 2025)
Salinity is one of the abiotic stresses that is most af fecting the agricultural sector and tomato cultivation in Mexico and the world. Some alternatives are being considered to counteract the ef fects of salinity, including the use of cation exchangers such as Si (Silicon). The present study aimed to evaluate the response in the germination process to the contribution of three doses of silicon, in dif ferent varieties of Solanum lycopersicum L. subjected to salt stress with NaCl. The study was carried out at the Seed Laboratory of the Department of Agronomy of the Autonomous University of Baja California Sur, Mexico under laboratory conditions. The variables associated with the germination and seedling morphology of three varieties of S. lycopersicum L. were considered, which were evaluated by a completely randomized design in a factorial arrangement with four replications for a total of 27 treatments, resulting from the interaction between varieties. (Cherry, Floradade and Rio Grande), NaCl (0, 25 and 50 mM) and Si (0, 1 and 2 mM). It was obtained that the germination percentage is conditioned by the variety factor and that the fresh biomass and the germination rate (%) are af fected by the 3k interaction (P ≤ 0.001). The Principal Component Analysis showed that NaCl and Si constitute response modulators in fresh and dry biomass accumulation, and root and stem development in S. lycopersicum seedlings under salt stress. It is concluded that there is a dif ferential response in the manifestation of salt stress depending on the phenological state of the plant and variety of S. lycopersicum, verifying the mitigating ef fect of Si in the seedling stage, but not in germination and related variables and indices.